Autoradiographic Technique for Screening Chemolithotrophic Hydrogen-Utilizing Bacteria - Gowda, T. K. S.; Watanabe, I. (Canadian Science Publishing, 1983)
A simple autoradiographic method for screening aerobic H2-dependent chemolithotrophs is described. Bacteria were grown on agar plates in ambient air at 32 °C. Colonies from the plates were inoculated to H2-uptake agar plates by replica plating or streaking and incubated for 14 days in a desiccator under 20% H2, 2% O2, 5% CO2, and the balance N2, or 2% O2, 5% CO2, and the balance N2. The plates were further incubated for 9 days with 14CO2 in the above gas mixtures. The colonies were transferred to muslin cloth by replica method and the cloth was exposed to X-ray film for autoradiography. H2 was necessary for CO2 fixation under autotrophic conditions. By this technique, the predominance of H2-utilizing facultative aerobic chemolithotrophs among wetland rice root isolates was confirmed. The strains of Azospirillum lipoferum tested were found to fix 14CO2, but the A. brasilense strains tested were unable to fix 14CO2.